Evaluation of the general farm characteristics and dairy herd structure in urban and peri-urban dairy production system in the Addis Ababa milk shed - Mekasha, Yoseph; Tegegne, Azage; Yami, A.; Umunna, N.N. (Ethiopian Society of Animal Production, 2003)
Evaluation of the general farm characteristics and dairy herd structure was undertaken in urban and peri-urban dairy production system in the Addis Ababa milk shed. A total of 41 dairy farms were selected randomly from three production sub-systems (intar-urban, large peri-urban and secondary town sub-systems), and cross sectional survey was implemented across all the production sub-systems. The result indicated that, female-headed family.owned 24.4% of the dairy farms, where the largest proportion was observed in intra-urban dairy farms (40%). The proportion of dairy farm owners being farmers was 34.2% followed by household wives (14.6%). About 78% of the dairy farm owners were literate (39% above secondary), while 22% were illiterate. The largest proportion of literate owners was found in large peri-urban, while the largest proportion of illiterate was found in intra-urban dairy farms. Most dairy farms (73.2%) were managed by the owner themselves and the type of cattle production is mainly dairying. All the dairy farms keep Holstein-Friesian as a dairy stock and the management system followed was intensive. The largest mean herd size ways observed, in large peri-urban dairy farms (128) followed by secondary town (9.1) and intra urban farms (9.2). The proportion of cows out of the total herd was 50%, where the largest proportion was observed in intra-urban (58%), dairy farms. The contribution of indigenous zebu cattle to the overall herd was only 2.5%. Milking cows contributed to 35.8% of the total herd and 72.2% of the total cows, where the largest was occurred in secondary town dairy farms. The proportion of heifers in the production system was 25.6% while the proportion of calves was 21.6%. The largest proportion of calves (88%) was found to be females.